In utero exposure to bisphenol A alters prostatic responses in adult male rats: Protective effects of melatonin (2020)
Exposure to bisphenol A (BPA), an endocrine disrupting chemical (EDC), has been shown to result in a number of reproductive dysfunction. Melatonin (MLT) is a potent antioxidant known to protect against EDC-induced toxicity. We aimed at investigating the protective effects of MLT on prostate gland dysfunction in the F1 adult male Wistar rats exposed to BPA in utero. Rats, confirmed pregnant were divided into five groups (n=5): Control: 0.2 ml canola oil; BPA 25 μg/kg/day; BPA 250 μg/kg/day; BPA 25 μg/kg/day + MLT 1 mg/kg/day and BPA 250 μg/kg/day + MLT 1 mg/kg/day. Blood sample was collected for serum hormonal and biochemical assays. Histopathology of the prostate gland was carried using standard methods. Prostatic index was significantly increased in BPA-treated rats compared to control (p˂0.05). BPA induced prostatic oxidative stress and caused significant decreases in the levels of serum T and LH but resulted in significant increases in the levels of PSA, PAC and TAC. Prostatic lesions observed in the BPA groups rats included hyperplasia (functional, reactive and atypical). These were attenuated in the rats co-treated with MLT. BPA induced marked prostatic alterations, while melatonin co-administration protected against these alterations.